(untitled) (Tzintzun, Revista de Estudios Históricos, 2021)
The present work points out how the music created during the emancipation process, originated in a traditional sonorous corpus which started to be persecuted in the second half of the 18th century due to the new Bourbon way of thinking. The way this corpus, with its discordant nature, became suitable to get implanted in the lyrics for and against the insurrection movement started in 1810 and finally, as some of its verses had the anti-Spanish germ how it was later used by the rising Mexican State as a means of creating an identity among the inhabitants.